Geochemical Assessment of Sediment Quality using Multivariate Statistical Analysis of Ennore Creek, North of Chennai, SE Coast of India - Jayaprakash, M.; Ramasamy, Nagarajan; Velmurugan, P.; Giridharan, L.; Neetha, V.; Urban, B. (University Putra Malaysia Press, 2014)
The composite nature of Ennore Creek, receiving polluted waters from Buckingham canal, River Kortalaiyar, and the presence of numerous industries rapidly degrade the coastal environment. In this study, multivariate statistical technique was used to assess the nature of pollution and to identify the factors responsible for the enrichment of trace metals in the creek sediments. Forty samples were collected during pre- and post-monsoon periods to evaluate the seasonal variations on the concentration of trace metals in the sediments. The results indicate that not much seasonal variation exists in the concentration of trace metals in the sediments of Ennore creek. Results of the cluster analysis illustrate that the enrichment of trace metals was mainly from anthropogenic sources. Meanwhile, correlation coefficient among the metals reveals that some of the metals (Fe and Al) derived were of natural origin. The complex data matrix of the sediment were interpreted after reduction to three factors and the results illustrate the extent of the influence of anthropogenic activities. The spatial distribution diagrams demonstrate and demarcate the region of enrichment of metals in the sediments of Ennore creek.